157 The population-level impact of exercise training programs to prevent sports injuries – a controlled ecological evaluation based on reductions in hospital-treated injuries. (1st September 2016) - Finch, Caroline F; Akram, Muhammad; Donaldson, Alex; Gabbe, Belinda; Lloyd, David; Cook, Jill
Abstract : Background: To date, there have been very few attempts at setting broad-based sports injury prevention public health activity. A staged and evidence-informed approach towards developing and delivering a new lower limb injury prevention program (FootyFirst) for community-level Australian football. The National Guidance for Australian football Partnerships for Safety (NoGAPS) study is one of the first large-scale studies to use a controlled, ecological design to assess the effectiveness of a sports injury prevention intervention at the population-level. The aim of this talk is to present the population-level evaluation of FootyFirst Methods: FootyFirst was implemented during the 2012 and 2013 football seasons and its impact on injury rate evaluated through a controlled ecological study design applied to three distinct geographic regions (R1-3). Each region received a different combination of program + delivery mode: Region 1 (R1)-Full FootyFirst program + fully supported delivery in both 2012 and 2013; R2-Full FootyFirst program + unsupported delivery (both 2012 and 2013); R3-No FootyFirst + no delivery in 2012 (control), full FootyFirst program + full delivery in 2013. For each region, the numbers of hospital-treated (admissions and emergency department presentations) sports injury cases at the hospitals serving those regions were obtained from routine data collections. The in-football season monthly number of lower limb injuries (#LLI) during 2006–2013 was modelled by an intervention time series. The sports injury data was "interrupted" at the beginning of 2012, to coincide with the starting of the FootyFirst delivery, and a second inter accounted for an administrative data change. The model was used to assess changes in slope of the trend lines pre- and post-intervention using a generalised least squares method. Results: There was a significant decline in #LLI after the first delivery of FootyFirst only for R1 (pre-FootyFirst monthly increase of 0.15 cases; post-FootyFirst monthly decline of 2.62 cases; effect p = 0.005).The administrative data change led to an increase in the number of cases in all regions. Conclusions: After adjusting for seasonal effects, there was a significant reduction in #LLI treated in hospitals in the region where FootyFirst was accompanied by full implementation support.